Pengembangan Paket Wisata Berbasis Pengalaman Di Desa Wisata Liya Togo, Wakatobi - Normayasari Normayasari; Nasrun Nasrun; La Ode Mansy; La Ode Muh. Norsa; Sariamin Sahari (Mathematics Education Study Program, 2025)
Liya Togo Tourism Village in Wakatobi possesses unique cultural and marine tourism potential, but it has not been optimally utilized. This research aims to develop experience-based tour packages that can maximize this potential and increase tourist visits. This research employs a descriptive qualitative approach with data collection methods through in-depth interviews, participatory observation, and documentation. The research results identify tourism potentials that can be integrated into experience-based tour packages, such as combining visits to historical sites with marine activities (snorkeling, diving), as well as interaction with local communities. This research also emphasizes the importance of community participation as a Community Based Tourism concept in tourism management and provides recommendations for tour package development strategies, promotion, and community capacity building to achieve sustainable tourism.